We must not think of ourselves : a novel [large type] - Grodstein, Lauren (Thorndike Press large print top shelf, 2024)
"On a November day in 1940, Adam Paskow becomes a prisoner in the Warsaw Ghetto, where the Jews of the city are cut off from their former lives and held captive by Nazi guards to await an uncertain fate. Weeks later, he is approached by a mysterious figure with a surprising request: Would he join a secret group of archivists working to preserve the truth of what is happening inside these walls? Adam agrees and begins taking testimonies from his students, friends, and neighbors. He learns about their childhoods and their daydreams, their passions and their fears, their desperate strategies for safety and survival. The stories form a portrait of endurance in a world where no choices are good ones. One of the people Adam interviews is his flatmate Sala Wiskoff, who is stoic, determined, and funny--and married with two children. Over the months of their confinement, in the presence of her family, Adam and Sala fall in love. As they desperately carve out intimacy, their relationship feels both impossible and vital, their connection keeping them alive. But when Adam discovers a possible escape from the Ghetto, he is faced with an unbearable choice: whom can he save, and at what cost?"--